2000
DOI: 10.1002/qj.49712656914
|View full text |Cite
|
Sign up to set email alerts
|

Deriving cloud overlap statistics from radar

Abstract: The predictions of general-circulation models (GCMs) are sensitive to the assumed cloud overlap within a vertical column of model grid boxes, but until now no reliable observations of the degree of cloud overlap have been available. In this note we derive the overlap characteristics of clouds from 71 days of high vertical resolution 94 GHz cloud radar data in the UK. It is found that, contrary to the assumption made in most models, vertically continuous clouds tend not to be maximally overlapped. Rather, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
209
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(221 citation statements)
references
References 12 publications
11
209
1
Order By: Relevance
“…In response, a new scheme for representing vertical cloud alignment, referred to as ''exponential-random'' overlap, was introduced by Hogan and Illingworth (2000). They defined an ''overlap parameter'', which allows the combined cloud cover of a pair of gridbox layers to take any value between that of maximum overlap and of random overlap.…”
Section: Parameterization Of Cloudsmentioning
confidence: 99%
“…In response, a new scheme for representing vertical cloud alignment, referred to as ''exponential-random'' overlap, was introduced by Hogan and Illingworth (2000). They defined an ''overlap parameter'', which allows the combined cloud cover of a pair of gridbox layers to take any value between that of maximum overlap and of random overlap.…”
Section: Parameterization Of Cloudsmentioning
confidence: 99%
“…Furthermore, research has been conducted to improve numerical model predictions by verifying and improving cloud radar data or through parameterization and data assimilation (Mace et al, 1998;Hogan and Illingworth, 2000;Ahlgrimm and Forbes, 2014). Moreover, other studies have considered the microphysical characteristics of clouds such as the liquid water content and size distribution of rain droplets (O'Connor et al, 2005;Zhong et al, 2012) and the classification of ice crystal forms in clouds (Aydin and Singh, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…As this combined overlap assumption is physically more reasonable than MO and RO, it has been adopted by most GCMs in recent times (Collins, 2001;Barker, 2008a). However, recent studies have found that MRO is still insufficient to fully describe the nature of cloud overlap: the overlap of vertically adjacent clouds is not simply a maximum, as in MRO, but changes depending on the depth of clouds (Hogan and Illingworth, 2000). Additionally, it should be noted that a common deficiency of MRO and RO is that they are sensitive to model vertical resolution (Räisänen, 1998;Bergman and Rasch, 2002), which causes different C tot and radiation output, even for the same cloud field and using the same overlap assumption.…”
Section: Conventional Cloud Overlap Assumptionsmentioning
confidence: 98%